2000
DOI: 10.1021/bp990139h
|View full text |Cite
|
Sign up to set email alerts
|

Design of Affinity Tags for One‐Step Protein Purification from Immobilized Zinc Columns

Abstract: Affinity tags are often used to accomplish recombinant protein purification using immobilized metal affinity chromatography. Success of the tag depends on the chelated metal used and the elution profile of the host cell proteins. Zn(II)-iminodiacetic acid (Zn(II)-IDA) may prove to be superior to either immobilized copper or nickel as a result of its relatively low binding affinity for cellular proteins. For example, almost all Escherichia coli proteins elute from Zn(II)-IDA columns between pH 7.5 and 7.0 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…These low values could be attributed to the presence of protein inhibitors in the samples [6]. Studies have suggested ways of removing these protein inhibitors such as the method which entails the use of immobilized metal affinity chromatography (IMAC) for binding the protease inhibitors and the soybean lectins from an aqueous extract of the flour [30]; [31]; [6]. The low protein contents of the samples could also be as a result of the presence of cassava flours that were added to the soybean as seen in their sealed containers.…”
Section: Microbial Analysis Of Soybean Powdermentioning
confidence: 99%
“…These low values could be attributed to the presence of protein inhibitors in the samples [6]. Studies have suggested ways of removing these protein inhibitors such as the method which entails the use of immobilized metal affinity chromatography (IMAC) for binding the protease inhibitors and the soybean lectins from an aqueous extract of the flour [30]; [31]; [6]. The low protein contents of the samples could also be as a result of the presence of cassava flours that were added to the soybean as seen in their sealed containers.…”
Section: Microbial Analysis Of Soybean Powdermentioning
confidence: 99%
“…Interestingly, there were a large number of proteins of the E. coli genome that bound to Zn +2 . Conventional thought requires multiple histidine residues in the correct spatial orientation for Zn +2 binding: again, this fact had been established by examining different zinc motifs via comparison of proteins that differ in histidine content and spatial orientation, and the identification of zinc affinity tails (Pasquinelli et al, 2000;Patwardhana et al, 1997;Beitle and Ataai, 1993). Therefore, although the equilibrium association constant between histidine and divalent zinc is low, there appears to be an unexpectedly large population of E. coli proteins capable of some binding to Zn +2 .…”
Section: Characteristics Of Tcpmentioning
confidence: 99%
“…Using rational design and in vitro evolution, researchers have introduced zinc binding sites into different protein structures such as four-helix bundles (Regan and Clarke, 1990), antibody light chain (Wade et al, 1993), triple-strand coiledcoil (Kiyokawa et al, 2004), and retinal binding protein (Muller and Skerra, 1994). Recently, zinc binding proteins have been engineered for more sophisticated tasks, for example, protein conformation switches (Cerasoli et al, 2005;Ambroggio and Kuhlman, 2006), biosensors (Shults et al, 2003), purification tags (Pasquinelli et al, 2000), control of oligomerization states (Phillips et al, 2010), catalytic zinc sites (Nomura and Sugiura, 2004), or even regulating a bacterial signal transduction pathway (Dwyer et al, 2003). And zinc fingers combined with restriction endonucleases or recominases have emerged as an important tool for molecular biology for their application in editing genomes (Miller et al, 2007;Wu et al, 2007;Proudfoot et al, 2011).…”
Section: Introductionmentioning
confidence: 99%